2018
DOI: 10.18632/oncotarget.25281
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of carfilzomib in relapsed and/or refractory multiple myeloma: systematic review and meta-analysis of 14 trials

Abstract: ObjectiveCarfilzomib (Carf) is a second-generation proteasome inhibitor approved for patients with relapsed and/or refractory multiple myeloma (RRMM) who failed ≥ 1 prior lines of therapy. We performed a systematic review of Carf literature with meta-analysis to determine the efficacy and safety in RRMM patients.MethodsBased on literature search, we included a total of 14 eligible phase I/II, phase II and phase III Carf based clinical trials. The cumulative incidence and odds ratios (OR) were calculated with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…(NCT02412878) trial, that compared RRMM patients treated with carfilzomib once a week (70 mg/m 2 ) or twice a week (27 mg/m 2 ), showed that weekly carfilzomib at 70 mg/m 2 significantly prolonged PFS, while in the control arm PFS and ORR were inferior to the phase III ASPIRE trial [20]. In a meta-analysis of 14 trials, combination regimens and higher carfilzomib dose offered better response with no significant extra toxicity [21]. Our data therefore confirm that in order to ensure the largest and deepest clinical benefit, carfilzomib should be administered without reduction and adverse events should be prevented and faced with a proactive management.…”
Section: Discussionmentioning
confidence: 99%
“…(NCT02412878) trial, that compared RRMM patients treated with carfilzomib once a week (70 mg/m 2 ) or twice a week (27 mg/m 2 ), showed that weekly carfilzomib at 70 mg/m 2 significantly prolonged PFS, while in the control arm PFS and ORR were inferior to the phase III ASPIRE trial [20]. In a meta-analysis of 14 trials, combination regimens and higher carfilzomib dose offered better response with no significant extra toxicity [21]. Our data therefore confirm that in order to ensure the largest and deepest clinical benefit, carfilzomib should be administered without reduction and adverse events should be prevented and faced with a proactive management.…”
Section: Discussionmentioning
confidence: 99%
“…Although fungal infection has recently been associated with ibrutinib, the cause has mostly been aspergillosis in the central nervous system or, much less frequently, disseminated Cryptococcus , mucormycosis, or Pneumocystis pneumonia (Ghez et al , ). Carfilzomib has not been associated with an increased incidence of fungal infections (Shah et al , ), and we are unaware of any literature reporting an increased incidence of infections with the carfilzomib/ibrutinib combination.…”
Section: Discussionmentioning
confidence: 87%
“…710 For instance, within the proteasome inhibitors, carfilzomib was shown to cause significantly more CVCs compared with bortezomib which is less cardiotoxic but causes neuropathy more frequently. 11 Similarly, among different tyrosine kinase inhibitors (TKIs), imatinib showed minimal CVCs, 7 while dasatinib 12 was associated with more cardiopulmonary issues, while ponatinib was associated with more vascular than cardiac events. 13 Of note, although many of these new drugs are supposedly targeted towards one gene, apart from a few drugs, most of the time other targets or the same target in other normal organs are also affected.…”
Section: Defining the Problemmentioning
confidence: 99%